Identification And Control Of Occupational Hazards In Traditional Yellow Tofu Production Using The HIRADC Method - Riny Yolandha Parapat; Nola Septiani Pramita; Siti Nayla Alifah (Indonesian Journal of Multidisciplinary on Social and Technology, 2026)
Traditional yellow tofu production involves various manual activities that may expose workers to occupational hazards if safety aspects are not properly managed. This study aims to identify occupational hazards and determine appropriate control measures in traditional yellow tofu production using the Hazard Identification, Risk Assessment, and Determining Control (HIRADC) method. The research was conducted at FMY Tofu Factory in Bandung, Indonesia, through direct observation, worker interviews, and documentation of production activities. Hazard identification was carried out at each production stage, including washing, soaking, grinding, boiling, filtering, coagulation, molding, re-boiling, and cutting. The identified hazards were classified into physical, ergonomic, mechanical, electrical, chemical, biological, and environmental hazards. Risk assessment was performed using likelihood and severity parameters to determine risk levels. The results identified 27 potential hazards with risk levels ranging from low to very high. Very high risks were mainly found in the grinding, boiling, and cutting stages due to exposure to rotating machinery, damaged electrical equipment, high temperatures, and sharp cutting tools. High risks were associated with slippery floors, repetitive manual handling, and awkward working postures. Recommended control measures include installing machine guards, improving ventilation and drainage systems, implementing ergonomic workstations, conducting routine electrical inspections, and providing appropriate personal protective equipment such as heat-resistant and cut-resistant gloves. The implementation of HIRADC provides a systematic approach to improving occupational safety and health conditions and reducing workplace accidents in traditional yellow tofu production.